2011
DOI: 10.3177/jnsv.57.22
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure Can Be Assessed by Fat-Free Mass in Female Athletes Regardless of Body Size

Abstract: Summary Energy requirements can be estimated from resting energy expenditure (REE). However, little is known about factors influencing REE in Japanese female athletes. This study was performed to evaluate the relationship between REE and body composition in Japanese female athletes with a wide range of body sizes. Ninety-three athletes (age 20.3 Ϯ 1.2 y, height 162.8 Ϯ 6.4 cm, body weight (BW) 57.0 Ϯ 9.2 kg, fat-free mass (FFM) 45.4 Ϯ 6.2 kg) were classified into three groups according to BW: small-size (S) ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…However, the explanation for this finding has yet to be uncovered. Taguchi et al (9) reported that organ-tissue mass is responsible for determining REE, and thus it can be accurately measured by FFM. The investigator utilized Japanese female athletes over a wide range of body sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the explanation for this finding has yet to be uncovered. Taguchi et al (9) reported that organ-tissue mass is responsible for determining REE, and thus it can be accurately measured by FFM. The investigator utilized Japanese female athletes over a wide range of body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The four organ-tissue compartments have a specific metabolic rate; BM and AT have relatively smaller weight-related metabolic rates (2.3 and 4.5 kcal/kg/d), on the other hand, SM and RM have higher metabolic rates (13 and 54 kcal/kg/d) (7). REEe can be obtained utilizing these metabolic rates with the actual mass of each organ-tissue compartment based on the previously established model (9,11). According to previous studies which used the same organ-tissue REE prediction method, the correlation coefficients between REEm and REEe were 0.75 (pϽ0.001) for untrained males and females, and 0.77 (pϽ0.01) for Japanese female athletes (7,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as for the four component model of REE prediction, Taguchi et al (2011) evaluated that the relationship between REE and body composition in Japanese female athletes with a wide range of body sizes. Their results indicated, in good agreement with previous study (Bosy-Westphal et al, 2004), that REE for female athletes with a wide range of body sizes can be attributed to changes in organ tissue mass, and not changes in organ tissue metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…The data used for the current analysis were collected from different 3 experimental studies that followed a similar methodology (Usui et al, 2009;Taguchi et al, 2011;Hasegawa et al, 2011). Total of 288 healthy women (216 young women; age: 21.8 ± 2.0 (18-29) years and 72 elderly women; age: 63.3 ± 6.4 (50-77) years) were recruited for the study.…”
Section: Subjectsmentioning
confidence: 99%